FISHERIES SANCTUARY PLANNING IN PRACTICE: LESSON LEARNT FROM ECOSYSTEM APPROACH TO FISHERIES MANAGEMENT IN NORTH KALIMANTAN PROVINCE - Andhika Prima Prasetyo; Asep Priatna; Agus Setiyawan; Rodo Lasnihora; Fadli Yahya; Dian Oktaviani; Duto Nugroho; Rudy Masuswo Purwoko; Nurmayanti Nurmayanti; Ersant Dirgantara; Hendri Antoro; Dahlan Burkiki (Indonesian Fisheries Research Journal, 2018)
Governor Decree of North Kalimantan No. 26 in 2014 concerning Management of Bombay Duck in the North Kalimantan Province Waters was established in order to address over-exploitation of bombay duck (Harpadon nehereus) population. Fisheries sanctuary is the feasible solution that was agreed by comprehensive stakeholder discussion. This research aims to extract and elaborate our experiences on establishing fisheries sanctuary in the Bangkudulis waters which focus on science communication and in the fisheries sanctuary planning. The acoustic and larva survey conducted to support the consensus and to proof the traditional ecological knowledge of the communities. The results showed that the proposed conservation area of the Bangkudulis waters has significant ecological function to ensure the sustainability of bombay duck population. The distribution and abundance of larva and juveniles were found higher in that area. The approach and challenges to deal with ecological and socio-economic aspects as well as recommendations were discussed in this paper.